Targeted therapy based on ubiquitin-specific proteases, signalling pathways and E3 ligases in non-small-cell lung cancer - Yang, Yu-Chen; Zhao, Can-Jun; Jin, Zhao-Feng; Zheng, Jin; Ma, Li-Tian (Frontiers in Oncology, 2023)
Lung cancer is one of the most common malignant tumours worldwide, with the highest mortality rate. Approximately 1.4 million deaths owing to lung cancer are reported annually; of which, 85% of deaths occur owing to non-small-cell lung cancer (NSCLC). At present, the conventional treatment methods for NSCLC include radiotherapy, chemotherapy, targeted therapy and surgery. However, drug resistance and tumour invasion or metastasis often lead to treatment failure. The ubiquitin–proteasome pathway (UPP) plays an important role in the occurrence and development of tumours. Upregulation or inhibition of proteins or enzymes involved in UPP can promote or inhibit the occurrence and development of tumours, respectively. As regulators of UPP, ubiquitin-specific proteases (USPs) primarily inhibit the degradation of target proteins by proteasomes through deubiquitination and hence play a carcinogenic or anticancer role. This review focuses on the role of USPs in the occurrence and development of NSCLC and the potential of corresponding targeted drugs, PROTACs and small-molecule inhibitors in the treatment of NSCLC.